The ability to think critically and creatively in learning - Sri Mulyani; Fatimah Fatimah (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
The ability to think critically and creatively and solve problems related to the lives of young people is important. This awareness needs to be the foundation in curriculum development with the advanced contextual learning. Therefore, educators need to seriously merancanng learning that conclusion is based on the learning process. Critical and creative thinking skills can be developed through learning activities. Capabilities include several things, including: (1) make a decision and issue wisely, (2) generate ideas or creation of creative and innovative, (3) address the ways of thinking that in a hurry, not transparent and narrow, (4 ) improve cognitive and affective aspects, (5) apply knowledge, experience, and skills to think in more practical either inside or outside the school, and (6) to be open to receive and give opinions to make a judgment based on reason and evidence, and dare to give a view and criticism.